2003
DOI: 10.1124/jpet.102.047837
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of a Novel Antiglaucoma Agent, Bimatoprost (AGN 192024)

Abstract: Replacement of the carboxylic acid group of prostaglandin (PG) F 2␣ with a nonacidic moiety, such as hydroxyl, methoxy, or amido, results in compounds with unique pharmacology. Bimatoprost (AGN 192024) is also a pharmacologically novel PGF 2␣ analog, where the carboxylic acid is replaced by a neutral ethylamide substituent. Bimatoprost potently contracted the feline lung parenchymal preparation (EC 50 value of 35-55 nM) but exhibited no meaningful activity in a variety of PG-sensitive tissue and cell preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(157 citation statements)
references
References 37 publications
(58 reference statements)
10
144
1
2
Order By: Relevance
“…Unlike PGF 2a and Butaprost, Bimatoprost did not upregulate Nur77 expression in human ciliary SM cells and TM cells and Nur77 would, therefore, be concluded to play no role in its ocular hypotensive effects. In our previous study, we found that Bimatoprost induced upregulation of Cyr61 gene expression in cat iris and human ciliary SM cells (Liang et al, 2003). In contrast to PGF 2a , Bimatoprost did not regulate either CTGF or Nur77 upregulation in human ciliary SM and TM cells.…”
Section: Y Liang Et Al Upregulation Of Orphan Nuclear Receptor Nur77mentioning
confidence: 81%
“…Unlike PGF 2a and Butaprost, Bimatoprost did not upregulate Nur77 expression in human ciliary SM cells and TM cells and Nur77 would, therefore, be concluded to play no role in its ocular hypotensive effects. In our previous study, we found that Bimatoprost induced upregulation of Cyr61 gene expression in cat iris and human ciliary SM cells (Liang et al, 2003). In contrast to PGF 2a , Bimatoprost did not regulate either CTGF or Nur77 upregulation in human ciliary SM and TM cells.…”
Section: Y Liang Et Al Upregulation Of Orphan Nuclear Receptor Nur77mentioning
confidence: 81%
“…Therefore, if 1 ml of eyedrops (41 drops) contains 0.3 mg of bimatoprost, 1 droplet contains 0.007 mg, and 7 droplets contain 0.049 mg or 49 μg. Based on the study of Woodward et al (6) , this dose was safe for the animals. Woodward et al (6) used 2 droplets of bimatoprost 0.1% daily in monkeys weighting 2 kg, and this dose showed traces of metabolic substances in the blood of the animals, ensuring that this dose was not toxic.…”
Section: Methodsmentioning
confidence: 99%
“…PGF2 Ü is synthesized by a route involving COX-2 but not COX-1, suggesting a new route leading to the synthesis of endogenous lipid amides which reduce the intraocular pressure (IOP). Bimatoprost differs from prostaglandins as it does not stimulate the prostanoid receptors, is not mitogenic, does not contract the human uterus, and is electrochemically neutral (5,6) Clinical studies have reported ocular and periocular adverse events in 15 to 45% of patients receiving daily doses of eyedrops for three months. In decreasing order of incidence, the most adverse effects observed were: conjunctival hyperemia, growth of eyelashes and ocular pruritus 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] On the other hand, its metabolite, bimatoprost-free acid ) is also shown to lower the IOP by interacting with prostanoid FP receptors, thus being classifi ed as a potent FP receptor agonist. [22][23][24] On the contrary, both latanoprost and and MRP5 on the human as well as rabbit primary corneal epithelial cells. [6][7][8] In addition, mRNA expression levels of other isoforms of MRP, MRP1 and MRP3, have been reported in the human cornea, though functional activity and localization still remain to be assessed.…”
Section: Hariharan Et Al 488mentioning
confidence: 99%